KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - B11111127, SUCI AGISTA BELLASARI (Jurnal Manajemen Update, 2015)
The purpose of this research was to determine the effect of investment decisions, financing decisions, and dividend policy to firm value  on against either partially or simultaneously on the company’s listed in the Indonesia Stock Exchange in 2010-2013. Samples of this research were the company’s listed in the Indonesia Stock Exchange in 2010-2013, according tothe required criteria as many as 23 companies. Variables examined include investment decisions (tottal asset growth) , financing decisions (debt to equity ratio) and   dividend policy (divident payout ratio) as independent variables and firm value (Tobin’s Q) as dependent variable. Data obtained through secondary data from IDX and analyzed using multiple regression. The results of the testing showed that a hypothetical simultaneous investment decisions (tottal asset growth) , financing decisions (debt to equity ratio) and  dividend policy (divident payout ratio) affect didn't significant on firm value (tobin’s) with a significance level of 0,000 < 0,05. Partially suggests that , financing decisions (debt to equity ratio) and dividend policy  (divident payout ratio) have significant effect on  firm value (Tobin’s Q) with a significance level of 0,002 and 0,000 smaller than 0,05. investment decisions (tottal asset growth) didn’t have significantly effect on firm value (Tobin’s Q) with a significance level 0,440>0,005.   Keywords : investment decisions (tottal asset growth) , financing decisions (debt to equity ratio), dividend policy (divident payout ratio), firm value (Tobin’s)